The Role of Guidance and Counseling in Addressing the Impact of Social Media on Adolescent Mental Health (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
This study aims to examine the influence of social media on adolescents’ mental health from the perspective of guidance and counseling. The research was conducted using a quantitative approach with questionnaires as the main instrument, supported by interviews to enrich the data. The collected data were analyzed using descriptive statistics and correlation analysis to determine the relationship between the intensity of social media use and indicators of mental health such as stress, anxiety, and self-esteem. The findings indicate that excessive use of social media has a significant negative impact on adolescents’ psychological well-being, while moderate and positive use may enhance social support and self-expression. The study concludes that guidance and counseling play a crucial role in helping adolescents develop digital literacy, emotional regulation, and healthy social interactions in the online environment